2018
DOI: 10.1002/cpt.981
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Polymyxin B

Abstract: Polymyxin B is used as a last treatment resort for multidrug-resistant Gram-negative bacterial infections. The objectives of this study were to examine the population pharmacokinetics of polymyxin B and investigate factor(s) influencing pharmacokinetic variability. Four serial blood samples each were collected from 35 adult patients at steady state. The concentrations of individual polymyxin B components were analyzed using a validated liquid chromatography / tandem mass spectrometry assay and combined to deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
55
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 22 publications
13
55
3
Order By: Relevance
“…With a low correlation coefficient ( Supplementary Figure 1), this study found CrCL was a statistical covariate of polymyxin B clearance (Equ. 6), which was in agreement with other studies (Avedissian et al, 2018;Manchandani et al, 2018). However, Manchandani et al (2018) ; tvV2, typical value of volume of peripheral compartment distribution (V2); tvCl, typical value of central compartment clearance (Cl); tvQ, typical value of inter-compartmental clearance (Q, Cl2); dCldCrCL, fixed parameter coefficient of creatinine clearance (CrCL) to Cl; wV, variance of inter-individual variability for V; CorrV-Cl, correlation between V and Cl; stdev0, standard deviation; NA, not applicable.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…With a low correlation coefficient ( Supplementary Figure 1), this study found CrCL was a statistical covariate of polymyxin B clearance (Equ. 6), which was in agreement with other studies (Avedissian et al, 2018;Manchandani et al, 2018). However, Manchandani et al (2018) ; tvV2, typical value of volume of peripheral compartment distribution (V2); tvCl, typical value of central compartment clearance (Cl); tvQ, typical value of inter-compartmental clearance (Q, Cl2); dCldCrCL, fixed parameter coefficient of creatinine clearance (CrCL) to Cl; wV, variance of inter-individual variability for V; CorrV-Cl, correlation between V and Cl; stdev0, standard deviation; NA, not applicable.…”
Section: Discussionsupporting
confidence: 93%
“…While, as for patients with renal dysfunction, the regime of 50 mg maintenance dose twice daily would be a better option. These observations were in agreement with a previous study, although it did not provide a dosing recommendation for patients with renal dysfunction by using a one-compartment model (Manchandani et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Polymyxin B is a cyclic polypeptide antibiotic that regained significant interest due to the inevitable appearance of MDR bacteria ( Rigatto et al., 2019 ). It is even being considered as last resort therapy against some intractable gram-negative bacteria ( Manchandani et al., 2018 ).…”
mentioning
confidence: 99%